"Frequency of A Very Rare 35delG Mutation in Two Ethnic Groups of Iranian Populations " - R Sasanfar; A Tolouei; A Hoseinipour; DD Farhud; M Dolati; L Hoghooghi Rad; M Montazer Zohour; M Ghadami; H Pour-Jafari; M Hashemzadeh Chaleshtori (Tehran University of Medical Sciences, 2004)
The 35delG mutation in the Connexin 26 gene (Cx26), at the DNFB1 locus is the most common mutation in the patients with autosomal recessive non-syndromic hearing loss (ARNSHL). We have studied a total of 224 deaf cases from 189 families in two populations of Iran (Sistan va Bluchestan and Hormozgan provinces) by prescreening nested PCR, polyacrylamide gel electrophoresis and consequent direct sequencing method for all cases. The aim of the present work was to find prevalence of GJB2 mutations in the populations studied. Four different GJB2 mutations including 35delG, W24X, R127H and (V27I + E114 G) were identified in 11 of 189 families (5.8%). Two polymorphisms (V27I and V153I) also were detected in 14 families. A polymorphism S86T was determined in all cases. Homozygote 35delG mutation was found only in 1 of 189 families (0.5%).The rate of Cx26 mutations found in this study was lower than other Iranian populations. So the cause of deafness in the populations studied remains to be detected in other loci or genes.